A narrow band microstrip bandpass filter for RF Front-End of an UWB RFID reader circuit - Hossain, A. K. M. Zakir; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (Penerbit UMT, Universiti Malaysia Terengganu (UMT), 2016)
Microstrip resonator based UWB chipless RFID tag needs a chirp for interrogation by its reader. An electronic mixer and a filter can be utilized to produce the chirp in simple way. The overall performance of generating the chirp mostly depends on the design of a narrow bandpass filter. In microwave UWB frequency, microstrip is successfully used to design a passive filter circuit since it is compact and cost effective. An electronic mixer produces a lot of frequencies, therefore, a sharp narrow band higher order filter is essential to extract a particular frequency. This frequency can be used as the chirp for the RF front-end of the reader. A sixth order elliptical bandpass filter has been designed on Taconic TLX-8 microwave substrate. A six stages microstrip filter has been utilized for the design which is simulated by using standard microwave simulation software to work in the UWB region. A number of mixer and filter pairs are practically used in the UWB reader circuit to separate the different desired frequencies. Each filter has insertion loss of -3dB and -3dB at lower and upper cutoff frequencies 7.86 GHz and 8.02 GHz respectively.